Developing numeracy in the workplace - FitzSimons, Gail E.; Wedege, Tine (NOMAD Nordic Studies in Mathematics Education, 2007)
Internationally, adult literacy and numeracy are in general recognized as cultural techniques. However, the two competences and their development are contested among politicians and researchers. Numeracy is often subsumed under literacy and/ or described in isolation from the situational context. Adult numeracy at work is often described unproblematically as transfer from school to workplace. With reference to Bernstein’s theoretical framework, we claim that adult numeracy on the labour market is a horizontal discourse, in contrast to the vertical discourse of mathematics. This article draws on the findings from an Australian study into numeracy in the context of chemical spraying and handling, utilising a methodology based on activity theory. The main findings are that mathematically straightforward skills become transformed into workplace numeracy competence, when the complexities associated with successful task completion as well as the supportive role of mediating artefacts and the workplace community of practice are taken into account.